Identification and validation of candidate genes for high calcium content in finger millet [Eleusine coracana (L.) Gaertn.] through genome-wide association study. (September 2022) - Sharma, Divya; Tiwari, Apoorv; Sood, Salej; Meher, P.K.; Kumar, Anil
Abstract: Calcium is one of the most important mineral elements required in adequate amounts in the diet for sound health. Improved intake of calcium in the diet is the most cost-effective way to overcome its deficiency. Finger millet [ Eleusine coracana (L.) Gaertn.] is an excellent model system for investigating the genetic control of calcium accumulation in crops because of the very high calcium content in its grains. Therefore, a set of 202 diverse global finger millet accessions were evaluated for grain calcium content in two diverse environments in India. Phenotypic measurements for grain calcium content showed wide variation among the accessions, which ranged from 53 to 454 mg per 100g grains. High throughput genotyping by sequencing (GBS) identified 2977 genome-wide high-quality SNPs for marker-trait association (MTA) analysis with respect to grain calcium content, days to maturity, and grain yield. We found 44 common SNP-trait associations using general and mixed linear models contributing 4.80–17.79% phenotypic variance for calcium trait, 5 and 1 common SNPs associated with grain yield and days to maturity expressing 5.52–13.12%, and 5.83–6.75% phenotypic variance, respectively. Among 44 MTA's for calcium content, two putative SNP marker sequences were found homologous to candidate genes viz., calmodulin-binding protein (CBP) and CBL-Interacting Protein Kinase7 (CIPK7) of Setaria italic (Foxtail millet), which might be playing a pivotal role in grain calcium accumulation. Differential expression analysis by qPCR showed that the two genes ( EcCBP and EcCIPK7 ) were highly expressed in high calcium genotypes (HCG) as compared to medium and low calcium genotypes (LCG). These two genes might be involved in regulating the activities of CaX exchanger and calmodulin (CAM) proteins resulting in high grain calcium accumulation. Graphical abstract: Image 1 Highlights: Wide variation from 53 to 454 mg/100g grains was observed for calcium content. GBS resulted in 2977 high-quality SNPs for MTA's in 202 finger millet accessions. GLM and MLM identified 44 common MTA's for calcium content in two environments. Two SNP marker sequences were orthologous to candidate genes for grain calcium. EcCBP and EcCIPK7 were highly expressed in high as compared low calcium genotypes.